Intravenous Immunoglobulin Therapy for Critically Ill COVID-19 Patients With Different Inflammatory Phenotypes: A Multicenter, Retrospective Study - Chen, Yan; Xie, Jianfeng; Wu, Wenjuan; Li, Shusheng; Hu, Yu; Hu, Ming; Li, Jinxiu; Yang, Yi; Huang, Tingrong; Zheng, Kun; Wang, Yishan; Kang, Hanyujie; et al. (Frontiers in Immunology, 2022)
Background: Benefits of intravenous immunoglobulin administration are controversial for critically ill COIVD-19 patients. Methods: We analyzed retrospectively the effects of immunoglobulin administration for critically ill COVID-19 patients. The primary outcome was 28-day mortality. Inverse probability of treatment weighting (IPTW) with propensity score was used to account for baseline confounders. Cluster analysis was used to perform phenotype analysis. Results: Between January 1 and February 29, 2020, 754 patients with complete data from 19 hospitals were enrolled. Death at 28 days occurred for 408 (54.1%) patients. There were 392 (52.0%) patients who received intravenous immunoglobulin, at 11(IQR 8, 16) days after illness onset; thirty percent of these patients received intravenous immunoglobulin prior to ICU admission. By unadjusted analysis, no difference was observed for 28-day mortality between the immunoglobulin and non-immunoglobulin groups. Similar results were found by propensity score matching (n=506) and by IPTW analysis (n=731). Also, IPTW analysis did not reveal any significant difference between hyperinflammation and hypo-inflammation phenotypes. Conclusion: No significant association was observed for use of intravenous immunoglobulin and decreased mortality of severe COVID- 19 patients. Phenotype analysis did not show any survival benefit for patients who received immunoglobulin therapy.